2020
DOI: 10.1111/nyas.14493
|View full text |Cite
|
Sign up to set email alerts
|

Severe hyperthyroidism without symptoms due to nonthyroidal illness in a child with acute hepatitis: case report and literature review

Abstract: While liver enzyme changes are frequently reported in hyperthyroidism, liver dysfunction itself can lead to alterations in thyroid hormone metabolism. However, the exact relationship between hyperthyroidism and liver dysfunction is unclear. We report an 11‐year‐old boy presenting with acute hepatitis of unknown etiology, who was incidentally found to have asymptomatic biochemical hyperthyroidism. Despite significant total and free T4 elevation, clinical evidence of thyrotoxicosis was absent. Thyroid I‐123 upta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 53 publications
1
0
0
Order By: Relevance
“…Previous studies demonstrated that HDF in GD is due to excessive T3 inducing hepatocyte death through activation of the mitochondrial-dependent apoptosis pathway [22][23][24][25]. Many researchers proposed that the injury mechanism seems to be relative hypoxia in the hepatic perivenular regions because of liver oxygen consumption without corresponding blood flow increase [26][27][28]. In this study, FT3 and FT4 were significantly increased in GD patients with HDF, which was consistent with a previous study [25].…”
Section: Discussionsupporting
confidence: 92%
“…Previous studies demonstrated that HDF in GD is due to excessive T3 inducing hepatocyte death through activation of the mitochondrial-dependent apoptosis pathway [22][23][24][25]. Many researchers proposed that the injury mechanism seems to be relative hypoxia in the hepatic perivenular regions because of liver oxygen consumption without corresponding blood flow increase [26][27][28]. In this study, FT3 and FT4 were significantly increased in GD patients with HDF, which was consistent with a previous study [25].…”
Section: Discussionsupporting
confidence: 92%